Aversive control versus stimulus control by punishment. Issue 1 (10th November 2022) - Shahan, Timothy A.; Sutton, Gabrielle M.; Nist, Anthony N.; Davison, Michael
Abstract : Estes (1944) reported that adding electric shock punishment to extinction hastened response suppression but that responding increased when shock was removed. This result contributed to a view that reinforcement and punishment are asymmetrical processes because punishment has only indirect and temporary suppressive effects. Azrin and Holz (1966) suggested the result might be interpreted instead as shock serving as a discriminative stimulus for the absence of reinforcement. Here, to further examine potential stimulus control by punishment in a similar preparation, two groups of rats initially responded for food plus punishment and a third group for food alone. Reinforcement was then removed for all groups for the remaining three phases. With P and N denoting punishment and no punishment, the four phases for the three groups were: P‐P‐N‐N, P‐N‐P‐N, and N‐P‐N‐N. We found some evidence for stimulus control by shock deliveries for group N‐P‐N‐N (as suggested by Azrin and Holz), but all other changes in responding appeared due to introduction or removal of the aversive properties of shock. Although punishment may indeed have temporary effects under many circumstances, we argue that the view that this implies asymmetrical reinforcement and punishment processes was based on the flawed assumption that reinforcement has direct strengthening effects.